Influence of exercise intensity and duration on functional and biochemical perturbations in the human heart - Stewart, G.; Yamada, A.; Haseler, Luke; Kavanagh, J.; Chan, J.; Koerbin, G.; Wood, C.; Sabapathy, S. (Wiley-Blackwell Publishing Ltd., 2016)
© 2016 The Physiological Society. Strenuous endurance exercise induces transient cardiac perturbations with ambiguous health outcomes. The present study investigated the magnitude and time-course of exercise-induced functional and biochemical cardiac perturbations by manipulating the exercise intensity-duration matrix. Echocardiograph-derived left (LV) and right (RV) ventr icular global longitudinal strain (GLS), and serum high-sensitivity cardiac troponin (hs-cTnI) concentration, were examined in 10 males (age: 27 ± 4 years; V?O2, peak : 4.0 ± 0.8 l min -1 ) before, throughout (50%, 75% and 100%), and during recovery (1, 3, 6 and 24 h) from two exercise trials. The two exercise trials consisted of 90 and 120 min of heavy- and moderate-intensity cycling, respectively, with total mechanical work matched. LVGLS decreased (P < 0.01) during the 90 min trial only, with reductions peaking at 1 h post (pre: -19.9 ± 0.6%; 1 h post: -18.5 ± 0.7%) and persisting for > 24 h into recovery. RVGLS decreased (P < 0.05) during both exercise trials with reductions in the 90 min trial peaking at 1 h post (pre: -27.5 ± 0.7%; 1 h post: -25.1 ± 0.8%) and persisting for > 24 h into recovery. Serum hs-cTnI increased (P < 0.01) during both exercise trials, with concentrations peaking at 3 h post but only exceeding cardio-healthy reference limits (14 ng l -1 ) in the 90 min trial (pre: 4.2 ± 2.4 ng l -1 ; 3 h post: 25.1 ± 7.9 ng l -1 ). Exercise-induced reductions in ventricular strain and increases in cardiac injury markers persist for 24 h following exercise that is typical of day-to-day endurance exercise training; however, the magnitude and time-course of this response can be altered by manipulating the intensity-duration matrix. Key points: Strenuous endurance exercise induces transient functional and biochemical cardiac perturbations that persist for 24-48 h. The magnitude and time-course of exercise-induced reductions in ventricular function and increases in cardiac injury markers are influenced by the intensity and duration of exercise. In a human experimental model, exercise-induced reductions in ventricular strain and increases in cardiac troponin are greater, and persist for longer, when exercise is performed within the heavy- compared to moderate-intensity exercise domain, despite matching for total mechanical work. The results of the present study help us better understand the dose-response relationship between endurance exercise and acute cardiac stress/injury, a finding that has implications for the prescription of day-to-day endurance exercise regimes.